Method for producing coated semiconductor nanoparticles
By coating semiconductor nanoparticles with a metal oxide using microwave irradiation, the method addresses the issue of fluorescence efficiency deterioration, resulting in stable and efficient nanoparticles for applications in wavelength conversion materials and light emitting devices.
Patent Information
- Application Number
- JP2020086918
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-05-18
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2040-05-18
AI Technical Summary
Semiconductor nanoparticles suffer from deterioration in fluorescence emission efficiency due to surface defects, oxidation reactions, and aggregation, especially when used in applications like wavelength conversion materials.
A method for manufacturing coated semiconductor nanoparticles involves coating a metal oxide on the surface of the nanoparticles using microwave irradiation of a metal oxide precursor, which enhances stability and suppresses fluorescence efficiency deterioration.
The method efficiently produces coated semiconductor nanoparticles with suppressed fluorescence efficiency deterioration, suitable for use in resin compositions, wavelength conversion materials, and light emitting devices, maintaining high reliability even under high temperature and high humidity conditions.
Smart Images

Figure 0007655703000001 
Figure 0007655703000002 
Figure 0007655703000003
Abstract
Description
[Technical field]
[0001] The present invention relates to coated semiconductor nanoparticles and methods for making same. [Background technology]
[0002] In nano-sized semiconductor particles, the energy levels of the semiconductor nanoparticles become discrete because the excitons generated by light absorption are confined in nano-sized spaces, and the band gap depends on the particle size. For this reason, the fluorescence emission of semiconductor nanoparticles is highly efficient and the emission spectrum is sharp.
[0003] In addition, because the band gap changes depending on the particle size, the emission wavelength can be controlled, and it is expected to be used as a wavelength conversion material for solid-state lighting and displays (Patent Document 1).
[0004] However, semiconductor nanoparticles are prone to surface defects such as dangling bonds, which can cause oxidation reactions due to oxygen and moisture, leading to the formation of new defect levels, which in turn degrades the fluorescence emission efficiency over time.
[0005] The fluorescence emission efficiency of currently available semiconductor nanoparticles can be adversely affected by heat, humidity, photoexcitation, and even aggregation of particles. Furthermore, depending on the application of wavelength conversion materials, such as those used in displays, they are dispersed in resins, etc., but it is known that semiconductor nanoparticles can experience aggregation and a decrease in stability in the resin, resulting in a decrease in the fluorescence emission efficiency.
[0006] In view of the above, a method has been proposed for suppressing the deterioration of the fluorescence emission efficiency of semiconductor nanoparticles by coating the surface of the semiconductor nanoparticles with a protective layer such as a metal oxide to improve stability.
[0007] For example, Patent Document 2 discloses a method for producing a composite in which semiconductor nanoparticles are dispersed in silica glass by depositing a silica glass layer through a stepwise reaction of a metal alkoxide on the surface of semiconductor nanoparticles. It is disclosed that such a production method can provide a composite containing semiconductor nanoparticles with high fluorescence emission efficiency and stability.
[0008] However, when the composite disclosed in Patent Document 2 is used as a wavelength converting material, it is necessary to further improve the fluorescence emission efficiency. Also, regarding stability, it is necessary to suppress the deterioration of the fluorescence emission efficiency under high temperature and high humidity conditions in addition to under room temperature and air atmosphere.
[0009] In addition, in Patent Document 3, an aqueous dispersion of semiconductor nanoparticles is added to an organic solvent in which a surfactant is dissolved, to form reverse micelles encapsulating the aqueous nanoparticle solution, and the reverse micelles are used as a reaction field for a metal oxide precursor to produce a glass composite in which nanoparticles are dispersed and fixed.
[0010] A glass composite exhibiting high fluorescence emission efficiency can be provided by the method of Patent Document 3. However, this production method has problems in that the reaction takes several days and a large amount of solvent and surfactant is used, making mass production and cost reduction difficult. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] JP 2012-022028 A [Patent Document 2] International Publication No. 2011 / 081037 [Patent Document 3] Patent No. 4403270 Summary of the Invention [Problem to be solved by the invention]
[0012] The present invention has been made to solve the above problems, and has an object to provide a method for efficiently producing coated semiconductor nanoparticles in which deterioration of fluorescence emission efficiency is suppressed. The present invention also provides coated semiconductor nanoparticles in which deterioration of fluorescence emission efficiency is suppressed. [Means for solving the problem]
[0013] The present invention has been made in order to achieve the above object, and provides a method for producing coated semiconductor nanoparticles, comprising a step of coating a surface of semiconductor nanoparticles with a metal oxide, The present invention provides a method for producing coated semiconductor nanoparticles, which comprises subjecting a metal oxide precursor to microwave irradiation treatment to coat the surfaces of the semiconductor nanoparticles with the metal oxide.
[0014] According to such a method for producing coated semiconductor nanoparticles, it is possible to efficiently produce coated semiconductor nanoparticles in which deterioration of the fluorescence emission efficiency is suppressed.
[0015] In this case, it is preferable that the coating step is carried out in the coexistence of the semiconductor nanoparticles and the metal oxide precursor, and the metal oxide precursor in the coexistence is subjected to the microwave irradiation treatment, thereby coating the surface of the semiconductor nanoparticles with the metal oxide.
[0016] This makes it possible to reliably coat the semiconductor nanoparticles with metal oxide, and thus makes it possible to more efficiently produce coated semiconductor nanoparticles in which deterioration of the fluorescence emission efficiency is further suppressed.
[0017] In this case, the semiconductor nanoparticles used in the coating step preferably include a semiconductor nanoparticle core and one or more semiconductor nanoparticle shells covering the semiconductor nanoparticle core.
[0018] This makes it possible to efficiently produce semiconductor nanoparticles that are excellent in fluorescence emission properties and stability.
[0019] In this case, the semiconductor nanoparticle core used in the coating process can be selected from ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, AgGaS2, AgInS2, AgGaSe2, AgInSe2, CuGaS2, CuGaSe2, CuInS2, CuInS2, ZnSiP2, ZnGeP2, CdSiP2, and CdGeP2, either alone, in the form of a single crystal, or in the form of a plurality of crystals, an alloy, or a mixed crystal.
[0020] These compounds have excellent fluorescent emission properties and stability, and therefore can be suitably used for the semiconductor nanoparticle core. Among these compounds, ZnSe, ZnTe, CdSe, CdS, and InP are particularly preferred in terms of fluorescent emission properties and stability.
[0021] In this case, the semiconductor nanoparticle shell used in the coating step is selected from the group consisting of ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, and InSb, either alone, in combination, as an alloy, or as a mixed crystal. Selected and It is preferable to do so.
[0022] In this way, it is possible to obtain semiconductor nanoparticles having a large band gap and low lattice mismatch with respect to the core material. Among these compounds, ZnSe, ZnS, CdSe, and CdS are particularly preferable from the viewpoints of improving the fluorescence emission efficiency and stability.
[0023] In this case, the coating step is preferably carried out in one or more solvents selected from the group consisting of a polar solvent, a non-polar solvent, and an ionic liquid.
[0024] These solvents can be suitably used as dispersion media for the semiconductor nanoparticles and the metal oxide precursor.
[0025] In this case, it is preferable that the solvent used in the coating step contains the non-polar solvent in a volume ratio of 90% or more.
[0026] In this way, the deterioration of the fluorescence emission efficiency during coating can be suppressed.
[0027] In this case, the non-polar solvent used in the coating step is preferably one or more of toluene, hexane, cyclohexane, benzene, and diethyl ether.
[0028] These non-polar solvents can further improve the dispersibility of the semiconductor nanoparticles.
[0029] In this case, the metal oxide precursor used in the coating step is preferably one or more selected from metal alkoxides, metal halides, and metal complexes.
[0030] These metal oxide precursors are highly reactive and can be suitably used to coat the surfaces of semiconductor nanoparticles as metal oxides.
[0031] In this case, the coating step is preferably carried out in the presence of an alkaline aqueous solution.
[0032] This makes it easier to control the thickness of the coating layer.
[0033] In this case, the coating step is preferably carried out in the presence of a surfactant.
[0034] In this way, the dispersibility of the metal oxide precursor is excellent.
[0035] In this case, the coating step is preferably carried out in the presence of alcohol.
[0036] In this way, the dispersibility of the metal oxide precursor is improved.
[0037] The processing time for the microwave irradiation treatment in the coating step is preferably in the range of 3 to 30 minutes, and more preferably in the range of 5 to 15 minutes.
[0038] Such a treatment time can prevent a decrease in the fluorescence emission efficiency.
[0039] The heating temperature in the microwave irradiation treatment in the coating step is preferably in the range of 40 to 100°C, and more preferably in the range of 50 to 80°C.
[0040] The reaction temperature in the microwave irradiation treatment varies depending on the solvent, but by setting the temperature in this range, it is possible to prevent deterioration of the fluorescence emission efficiency.
[0041] In this case, it is preferable to include a step of modifying the surfaces of the semiconductor nanoparticles with a surface modifier prior to the coating step.
[0042] In this manner, the metal oxide precursor reacts on the surface of the semiconductor nanoparticles via the surface modifier, so that the metal oxide layer is more efficiently coated on the surface of the semiconductor nanoparticles, and deterioration of the fluorescence emission efficiency during microwave irradiation treatment is suppressed.
[0043] In this case, it is preferable that the surface modifier is one or more selected from (3-aminopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane, (3-mercaptopropyl)trimethoxysilane, (3-mercaptopropyl)triethoxysilane, 6-mercapto-1-hexanol, mercaptoacetic acid, 3-mercaptopropionic acid, and 4-mercaptobenzoic acid.
[0044] These compounds can be suitably used as surface modifiers.
[0045] The present invention also provides coated semiconductor nanoparticles in which the surface of the semiconductor nanoparticles is coated with a metal oxide, The metal oxide is coated on the surface of the semiconductor nanoparticles by microwave irradiation treatment to provide coated semiconductor nanoparticles.
[0046] Such coated semiconductor nanoparticles are suppressed from deteriorating in fluorescence emission efficiency.
[0047] In this case, it is preferable to prepare a resin composition in which the coated semiconductor nanoparticles are dispersed in a resin.
[0048] Such a resin composition is a resin composition in which the deterioration of the fluorescent light emission efficiency is suppressed.
[0049] In this case, it is preferable to use a cured product of the resin composition as the wavelength converting material.
[0050] Such a wavelength converting material has improved reliability.
[0051] In this case, it is preferable to use a wavelength conversion material as the light emitting element.
[0052] Such a light emitting element has particularly excellent reliability. Effect of the Invention
[0053] As described above, according to the method for producing coated semiconductor nanoparticles of the present invention, coated semiconductor nanoparticles in which deterioration of fluorescence emission efficiency is suppressed can be efficiently produced. Furthermore, the coated semiconductor nanoparticles of the present invention are coated semiconductor nanoparticles in which deterioration of fluorescence emission efficiency is suppressed. Furthermore, the coated semiconductor nanoparticles of the present invention can be suitably used in a resin composition, a wavelength conversion material using a cured product of the resin composition, and a light-emitting element using the wavelength conversion material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0054] Hereinafter, embodiments of the present invention will be described. However, in the present invention, the composition and production method of the semiconductor nanoparticles and metal oxide are not limited to the following embodiments.
[0055] As described above, there is a problem of efficiently producing semiconductor nanoparticles in which deterioration of fluorescence emission efficiency is suppressed. The present inventors have conducted intensive research into the above problem. As a result, they have found that coated semiconductor nanoparticles in which deterioration of fluorescence emission efficiency is suppressed can be efficiently produced by a method for producing coated semiconductor nanoparticles, which includes a step of coating the surfaces of semiconductor nanoparticles with a metal oxide, and the coating step is performed by a microwave irradiation treatment, and have completed the present invention.
[0056] That is, the present invention is a method for producing coated semiconductor nanoparticles, which includes a step of coating the surfaces of semiconductor nanoparticles with a metal oxide, and in which a metal oxide precursor is subjected to a microwave irradiation treatment to coat the surfaces of the semiconductor nanoparticles with the metal oxide.
[0057] The present inventors speculate that the mechanism by which the above problems are solved is as follows. In the case of coating the surface of semiconductor nanoparticles with metal oxides using the Stöber method or the reverse micelle method, the semiconductor nanoparticles coexist with water and oxygen for a long period of time, which causes oxidation reactions on the particle surface and aggregation of particles due to ligand detachment, gradually deteriorating the fluorescence emission efficiency.
[0058] On the other hand, in the method using microwave irradiation, the metal oxide precursor is selectively heated directly from the inside, and the reaction proceeds in a short time. This allows the metal oxide coating to proceed efficiently under mild conditions, mitigating the desorption of ligands adsorbed on the semiconductor nanoparticle (quantum dot) surface and surface oxidation reactions, and suppressing the deterioration of the fluorescence emission efficiency.
[0059] Therefore, by subjecting a metal oxide precursor to microwave irradiation treatment and coating the surface of the semiconductor nanoparticles with the metal oxide, it is possible to mitigate ligand detachment and surface oxidation reactions, thereby suppressing deterioration in the fluorescence emission efficiency.
[0060] The above mechanism is based on speculation, and whether it is correct or not does not affect the technical scope of the present invention.
[0061] (Semiconductor nanoparticles) The structure of the semiconductor nanoparticles in the present invention is not particularly limited, but from the viewpoint of fluorescence emission properties and stability, semiconductor nanoparticles having a core / shell structure are preferred. That is, it is preferable that the semiconductor nanoparticles include a semiconductor nanoparticle core and one or more semiconductor nanoparticle shells covering the semiconductor nanoparticle core. In semiconductor nanoparticles having a core / shell structure in which a nano-sized semiconductor particle is used as the core and a semiconductor having a larger band gap and lower lattice mismatch than the core is used as the shell, excitons generated in the shell are confined inside the core particle, improving the fluorescence emission efficiency, and further improving the stability since the core surface is covered with the shell.
[0062] Core / shell semiconductor nanoparticles Semiconductor Nanoparticle Core The material for is not particularly limited, but it is preferable to use, for example, a II-VI compound, a III-V compound, a I-III-VI compound, or a II-IV-V compound selected alone, multiple compounds, an alloy, or a mixed crystal.
[0063] Specific core materials include compounds containing ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, InSb, AgGaS2, AgInS2, AgGaSe2, AgInSe2, CuGaS2, CuGaSe2, CuInS2, CuInS2, ZnSiP2, ZnGeP2, CdSiP2, and CdGeP2. These compounds have excellent fluorescent emission properties and stability, and therefore can be suitably used for the semiconductor nanoparticle core. Among these compounds, ZnSe, ZnTe, CdSe, CdS, and InP are particularly preferred in terms of fluorescent emission properties and stability.
[0064] Semiconductor Nanoparticle Shell The material for is not particularly limited, but is preferably one having a large band gap and low lattice mismatch with respect to the core material, and is preferably a II-VI compound or a III-V compound selected alone, multiple, alloy, or mixed crystal.
[0065] Specific shell compounds include compounds containing ZnS, ZnSe, ZnTe, CdS, CdSe, CdTe, AlN, AlP, AlAs, AlSb, GaN, GaP, GaAs, GaSb, InN, InP, InAs, and InSb, and these compounds can have a large band gap and low lattice mismatch with the core material. Among these compounds, ZnSe, ZnS, CdSe, and CdS are particularly preferred in terms of improving the fluorescence emission efficiency and stability.
[0066] There are various methods for producing semiconductor nanoparticles, such as a liquid phase method and a gas phase method, but the present invention is not particularly limited to these. From the viewpoint of exhibiting high fluorescence emission efficiency, it is preferable to use semiconductor nanoparticles obtained by a hot soap method or a hot injection method, in which a precursor species is reacted at high temperature in a non-polar solvent with a high boiling point.
[0067] In addition, in order to reduce surface defects, it is preferable that the semiconductor nanoparticles have organic ligands called ligands coordinated to the surface. From the viewpoint of suppressing aggregation of the semiconductor nanoparticles, it is preferable that the ligand contains an aliphatic hydrocarbon. Examples of such ligands include oleic acid, stearic acid, palmitic acid, myristic acid, lauric acid, decanoic acid, octanoic acid, oleylamine, stearyl (octadecyl)amine, dodecyl (lauryl)amine, decylamine, octylamine, octadecanethiol, hexadecanethiol, tetradecanethiol, dodecanethiol, decanethiol, octanethiol, trioctylphosphine, trioctylphosphine oxide, triphenylphosphine, triphenylphosphine oxide, tributylphosphine, and tributylphosphine oxide, and these may be used alone or in combination.
[0068] (Coated semiconductor nanoparticles) In the method for producing coated semiconductor nanoparticles of the present invention, a metal oxide precursor is irradiated with microwaves to coat the surfaces of semiconductor nanoparticles with a metal oxide. By using microwaves, the metal oxide precursor is heated directly from the inside, and the coating proceeds selectively in a shorter time.
[0069] Here, the term "microwave" generally refers to electromagnetic waves having a frequency of 300 MHz to 3 THz. In addition, examples of a method for irradiating microwaves include, but are not limited to, a method using flexi WAVE manufactured by Milestone Corporation.
[0070] In the present invention, silicon oxide is included in the metal oxide.
[0071] The "coating" of metal oxide on the surface of semiconductor particles in the method for producing coated semiconductor nanoparticles of the present invention may be in the form of partial or complete coating. It may be a uniform coating layer such as a core-shell structure, or a non-uniform coating layer, or a structure in which multiple semiconductor nanoparticles are coated with metal oxide. The film thickness of the metal oxide is not particularly limited, but is preferably 100 nm or less from the viewpoint of light transmittance.
[0072] In this case, it is preferable to carry out the coating step in the presence of the semiconductor nanoparticles and the metal oxide precursor, and to coat the surfaces of the semiconductor nanoparticles with the metal oxide by irradiating the metal oxide precursor in the presence of the semiconductor nanoparticles with microwaves. This ensures that the metal oxide is coated on the semiconductor nanoparticles, and allows the efficient production of coated semiconductor nanoparticles in which the deterioration of the fluorescence emission efficiency is further suppressed.
[0073] In this case, it is preferable to select one or more of polar solvents, non-polar solvents, and ionic liquids as the dispersion medium for the semiconductor nanoparticles and metal oxide precursor in the coating step, and to perform the coating in the solvent. These solvents can be suitably used as the dispersion medium for the semiconductor nanoparticles and metal oxide precursor.
[0074] In this case, it is preferable that the ratio of the non-polar solvent in the solvent is 90% or more by volume, which can suppress the deterioration of the fluorescence emission efficiency during coating.
[0075] In addition, the non-polar solvent used in the coating step is preferably one or more of toluene, hexane, cyclohexane, benzene, and diethyl ether. These non-polar solvents can further improve the dispersibility of semiconductor nanoparticles. In addition, when the solvent is a non-polar solvent, a heating element that absorbs microwaves, called a Weflon, may be optionally used in the coating step.
[0076] The metal oxide precursor is not particularly limited, but it is preferable to use one or more selected from metal alkoxides, metal halides, and metal complexes. These metal oxide precursors are highly reactive and suitable for coating the surfaces of semiconductor nanoparticles as metal oxides.
[0077] Metal alkoxide compounds include tetramethyl orthosilicate, tetraethyl orthosilicate, tetrapropyl orthosilicate, tetraisopropyl orthosilicate, tetrabutyl orthosilicate, tetrakis(2-ethylhexyloxy)silane, trimethoxysilane, triethoxysilane, (3-aminopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane, (3-mercaptopropyl)trimethoxysilane, (3-mercaptopropyl)triethoxysilane, titanium ethoxide, titanium tetra isopropoxide, titanium tetrabutoxide, titanium tetraisobutoxide, tetrakis(2-ethylhexyl)orthotitanate, zinc isopropoxide, zinc tert-butoxide, zirconium ethoxide, zirconium propoxide, zirconium butoxide, aluminum ethoxide, aluminum isopropoxide, aluminum tert-butoxide, aluminum sec-butoxide, yttrium isopropoxide, hafnium ethoxide, hafnium tert-butoxide, iron ethoxide, and iron isopropoxide.
[0078] Examples of metal halide compounds include titanium chloride, zinc chloride, silicon tetrachloride, zirconium chloride, aluminum chloride, yttrium chloride, iron (II) chloride, iron (III) chloride, titanium bromide, zinc bromide, zirconium bromide, hafnium bromide, aluminum bromide, yttrium bromide, iron (II) bromide, iron (III) bromide, titanium iodide, zinc iodide, silicon tetraiodide, zirconium iodide, hafnium iodide, aluminum iodide, yttrium iodide, iron (II) iodide, and iron (III) iodide.
[0079] Examples of the metal complex compounds include aluminum acetylacetonate, titanyl acetylacetonate, iron (III) acetylacetonate, zinc acetylacetonate, and zirconium acetylacetonate.
[0080] From the viewpoint of stability, the metal oxide precursor is preferably a silicon alkoxide, an aluminum alkoxide, a zirconium alkoxide, or a titanium alkoxide. The mixing ratio (weight ratio) of the semiconductor nanoparticles to the metal oxide precursor is preferably 1:0.4 to 1:3.
[0081] In this case, it is preferable to use a catalyst to promote the reaction of the metal oxide precursor during the coating process. In particular, when a metal alkoxide is used, it is preferable to use a catalyst to promote the sol-gel reaction. Examples of the catalyst include an acidic aqueous solution or a basic aqueous solution, and a basic aqueous solution is particularly preferable from the viewpoint of the film thickness of the coating layer. The mixing ratio (molar ratio) of the catalyst to the metal oxide precursor is preferably 1:0.4 to 1:2, and the mixing ratio (molar ratio) of the metal oxide precursor to water is preferably 1:2 to 1:10.
[0082] In addition, in the coating process, it is preferable to use a surfactant from the viewpoint of dispersibility of the metal oxide precursor. The surfactant is not particularly limited, but examples thereof include quaternary ammonium salts such as cetyltrimethylammonium bromide, which are cationic surfactants, carboxylates and sulfonates, which are anionic surfactants, and polyoxyethylene alkyl ethers, which are nonionic surfactants. In terms of dispersibility of the metal oxide precursor, cationic surfactants are particularly preferable. The surfactant may be added as it is, or may be dissolved in a polar solvent such as alcohol, which will be described later, and added as a solution.
[0083] In addition, it is preferable to carry out the coating step in the presence of alcohol. If coating is carried out in the presence of alcohol, the dispersibility of the metal oxide precursor is more excellent. In addition, when a surfactant is added, dispersibility can be further improved by dissolving it in a polar solvent such as alcohol.
[0084] It is also preferable to include a step of modifying the surfaces of the semiconductor nanoparticles with a surface modifier before the coating step. process This allows the metal oxide precursor to react on the surface of the semiconductor nanoparticles via the surface modifier, resulting in a more efficient coating of the metal oxide layer on the surface of the semiconductor nanoparticles, and suppresses deterioration of the fluorescence emission efficiency during microwave irradiation treatment.
[0085] The surface modifier is preferably a compound having a molecule at one end containing an SH group or an NH2 group, which is a substituent that adsorbs to the surface of the semiconductor nanocrystal particle, and at the other end containing a -Si(OR)3 group (R: an alkyl group having 4 or less carbon atoms), an OH group, a COOH group, etc., which is a substituent that reacts with the metal oxide precursor. Examples of the surface modifier include (3-aminopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane, (3-mercaptopropyl)trimethoxysilane, (3-mercaptopropyl)triethoxysilane, 6-mercapto-1-hexanol, mercaptoacetic acid, 3-mercaptopropionic acid, and 4-mercaptobenzoic acid, and may be used alone or in combination. The atmosphere during modification with the surface modifier is not particularly limited, and is carried out under an inert gas atmosphere such as nitrogen, for example.
[0086] In this case, the reaction temperature in the microwave irradiation treatment differs depending on the solvent, but is preferably 40 to 100°C, more preferably 50 to 80°C, from the viewpoint of preventing deterioration of the fluorescence emission efficiency.
[0087] In this case, the treatment time in the microwave irradiation treatment is preferably 3 to 30 minutes, more preferably 5 to 15 minutes, from the viewpoint of preventing a decrease in the fluorescence emission efficiency.
[0088] The present invention also provides coated semiconductor nanoparticles in which a surface of a semiconductor nanoparticle is coated with a metal oxide, comprising: The metal oxide is coated on the surface of the semiconductor nanoparticles by microwave irradiation treatment to provide coated semiconductor nanoparticles.
[0089] The coated semiconductor nanoparticles of the present invention are semiconductor nanoparticles whose surfaces are coated with a metal oxide by microwave treatment. In such coated semiconductor nanoparticles of the present invention, the deterioration of the fluorescence emission efficiency is suppressed. Examples of the semiconductor nanoparticles and metal oxides include the semiconductor nanoparticles and metal oxides described above.
[0090] The microwave irradiation treatment coating of the present invention refers to coating the surface of semiconductor nanoparticles with a metal oxide irradiated with microwaves. The microwaves are as described above.
[0091] It is also preferable to use the coated semiconductor nanoparticles as a resin composition dispersed in a resin, which can provide a resin composition in which deterioration of the fluorescence emission efficiency is suppressed.
[0092] The resin material is not particularly limited, but may be a coating. semiconductor It is preferable that the nanoparticles do not aggregate and the fluorescence emission efficiency does not deteriorate, and examples of such materials include silicone resin, acrylic resin, epoxy resin, urethane resin, fluororesin, etc. These materials preferably have high transmittance in order to increase the fluorescence emission efficiency as a wavelength conversion material, and a transmittance of 80% or more is particularly preferable.
[0093] It is also preferable to use a cured product of the resin composition as the wavelength converting material. Such a wavelength converting material has improved reliability. The wavelength converting material may be used as it is or may be processed. For example, one form is a wavelength conversion film in which the composite is dispersed in the resin by processing into a sheet and then curing.
[0094] The method for producing the wavelength converting material is not particularly limited. For example, a resin composition in which coated semiconductor nanoparticles are dispersed in a resin can be applied to a transparent film such as PET or polyimide, cured, and laminated to obtain the wavelength converting material.
[0095] The resin layer can be formed by coating on the transparent film using a spraying method such as a spray or inkjet, a spin coat method, a bar coater method, or a doctor blade method. The thickness of the resin layer and the transparent film is not particularly limited and can be appropriately selected depending on the application.
[0096] The method for curing the resin composition is not particularly limited, but for example, the resin composition can be cured by heating the film on which the resin composition is applied at 60° C. for 2 hours and then at 150° C. for 4 hours.
[0097] Furthermore, it is preferable to use the wavelength converting material as a light emitting element. The light emitting element is not particularly limited, but may be a light emitting diode. A light emitting element using such a wavelength converting material has particularly excellent reliability. EXAMPLES
[0098] The present invention will be specifically described below using examples and comparative examples, but the present invention is not limited to these.
[0099] (Evaluation of luminescence properties) In the Production Examples and Examples, the fluorescence emission properties of the semiconductor nanoparticles were evaluated by measuring the fluorescence emission efficiency (internal quantum efficiency) at an excitation wavelength of 450 nm using a quantum efficiency measurement system (QE-2100) manufactured by Otsuka Electronics Co., Ltd.
[0100] (Production of semiconductor nanoparticles) (Production Example 1) In a flask, 0.070g (0.24mmol) of indium acetate, 0.256g (0.72mmol) of palmitic acid, and 4.0mL of 1-octadecene were added, and the mixture was heated and stirred at 100℃ under reduced pressure for 1 hour while dissolving. After cooling the flask to room temperature, nitrogen was purged, and 0.50mL (0.17mmol) of a 10vol% (tris)trimethylsilylphosphine / octadecene solution was added to the flask. The flask was heated to 300℃ and stirred for 20 minutes to synthesize InP semiconductor core particles.
[0101] Next, after cooling the flask to 200°C, 4.0mL (1.2mmol) of 0.30M zinc stearate / octadecene solution was added and stirred for 30 minutes. Furthermore, 0.60mL (0.90mmol) of 1.5M selenium / trioctylphosphine solution was added to the flask and stirred for 30 minutes. Next, after cooling the flask to room temperature, 0.22g (1.1mmol) of zinc acetate was added, and the mixture was heated and stirred at 100°C under reduced pressure, and degassed for 1 hour while dissolving. After purging the flask with nitrogen, it was heated to 230°C, 0.48mL (2.0mmol) of 1-DDT (dodecanethiol) was added, and stirred for 30 minutes.
[0102] The resulting solution was cooled to room temperature, ethanol was added, and the solution was centrifuged to precipitate the semiconductor nanoparticles and remove the supernatant. Toluene was then added to the precipitate to disperse it, and ethanol was added again, followed by centrifugation, the supernatant was removed, and the precipitate was redispersed in toluene to prepare a toluene solution of InP / ZnSe / ZnS semiconductor nanoparticles. The fluorescence efficiency of the solution was 76%.
[0103] (Production Example 2) In a flask, 0.070g (0.24mmol) of indium acetate, 0.256g (0.72mmol) of palmitic acid, and 4.0mL of 1-octadecene were added, and the mixture was heated and stirred at 100℃ under reduced pressure for 1 hour while dissolving. After cooling the flask to room temperature, nitrogen was purged, and 0.50mL (0.17mmol) of a 10vol% (tris)trimethylsilylphosphine / octadecene solution was added to the flask. The flask was heated to 300℃ and stirred for 20 minutes to synthesize InP semiconductor core particles.
[0104] Next, after cooling the flask to 200°C, 4.0mL (1.2mmol) of 0.30M zinc stearate / octadecene solution was added and stirred for 30 minutes. Furthermore, 0.60mL (0.90mmol) of 1.5M selenium / trioctylphosphine solution was added to the flask and stirred for 30 minutes. Next, after cooling the flask to room temperature, 0.22g (1.1mmol) of zinc acetate was added, and the mixture was heated and stirred at 100°C under reduced pressure, and degassed for 1 hour while dissolving. After purging the flask with nitrogen, it was heated to 230°C, 0.48mL (2.0mmol) of 1-DDT was added and stirred for 30 minutes. Furthermore, 0.70mL (3.0mmol) of (3-aminopropyl)triethoxysilane was added to the flask and stirred for 30 minutes.
[0105] The resulting solution was cooled to room temperature, ethanol was added, and the solution was centrifuged to precipitate the semiconductor nanoparticles and remove the supernatant. Toluene was then added to the precipitate, the solution was centrifuged, the supernatant was removed, and the solution was redispersed in toluene to prepare a toluene solution of InP / ZnSe / ZnS semiconductor nanoparticles. The fluorescence efficiency of the solution was 75%.
[0106] (Production Example 3) In a flask, 0.070g (0.24mmol) of indium acetate, 0.256g (0.72mmol) of palmitic acid, and 4.0mL of 1-octadecene were added, and the mixture was heated and stirred at 100℃ under reduced pressure for 1 hour while dissolving. After cooling the flask to room temperature, nitrogen was purged, and 0.50mL (0.17mmol) of a 10vol% (tris)trimethylsilylphosphine / octadecene solution was added to the flask. The flask was heated to 300℃ and stirred for 20 minutes to synthesize InP semiconductor core particles.
[0107] Next, after cooling the flask to 200°C, 4.0mL (1.2mmol) of 0.30M zinc stearate / octadecene solution was added and stirred for 30 minutes. Furthermore, 0.60mL (0.90mmol) of 1.5M selenium / trioctylphosphine solution was added to the flask and stirred for 30 minutes. Next, after cooling the flask to room temperature, 0.22g (1.1mmol) of zinc acetate was added, and the mixture was heated and stirred at 100°C under reduced pressure, and degassed for 1 hour while dissolving. After purging the flask with nitrogen, it was heated to 230°C, 0.48mL (2.0mmol) of 1-DDT was added and stirred for 30 minutes. Furthermore, 0.72mL (3.0mmol) of (3-mercaptopropyl)triethoxysilane was added to the flask and stirred for 30 minutes.
[0108] The resulting solution was cooled to room temperature, ethanol was added, and the solution was centrifuged to precipitate the semiconductor nanoparticles and remove the supernatant. Toluene was then added to the precipitate to disperse it, and ethanol was added again, followed by centrifugation, the supernatant was removed, and the precipitate was redispersed in toluene to prepare a toluene solution of InP / ZnSe / ZnS semiconductor nanoparticles. The fluorescence efficiency of the solution was 74%.
[0109] (Production Example 4) In a flask, 0.070g (0.24mmol) of indium acetate, 0.256g (0.72mmol) of palmitic acid, and 4.0mL of 1-octadecene were added, and the mixture was heated and stirred at 100℃ under reduced pressure for 1 hour while dissolving. After cooling the flask to room temperature, nitrogen was purged, and 0.50mL (0.17mmol) of a 10vol% (tris)trimethylsilylphosphine / octadecene solution was added to the flask. The flask was heated to 300℃ and stirred for 20 minutes to synthesize InP semiconductor core particles.
[0110] Next, after cooling the flask to 200°C, 4.0mL (1.2mmol) of 0.30M zinc stearate / octadecene solution was added and stirred for 30 minutes. Furthermore, 0.60mL (0.90mmol) of 1.5M selenium / trioctylphosphine solution was added to the flask and stirred for 30 minutes. Next, after cooling the flask to room temperature, 0.22g (1.1mmol) of zinc acetate was added, and the mixture was heated and stirred at 100°C under reduced pressure, and degassed for 1 hour while dissolving. After purging the flask with nitrogen, it was heated to 230°C, 0.48mL (2.0mmol) of 1-DDT was added, and stirred for 30 minutes. Furthermore, 0.35mL (1.5mmol) of (3-aminopropyl)triethoxysilane and 0.36mL (1.5mmol) of (3-mercaptopropyl)triethoxysilane were added to the flask and stirred for 30 minutes.
[0111] The resulting solution was cooled to room temperature, ethanol was added, and the solution was centrifuged to precipitate the semiconductor nanoparticles and remove the supernatant. Toluene was then added to the precipitate to disperse it, and ethanol was added again, followed by centrifugation, the supernatant was removed, and the precipitate was redispersed in toluene to prepare a toluene solution of InP / ZnSe / ZnS semiconductor nanoparticles. The fluorescence efficiency of the solution was 74%.
[0112] The above Production Examples 1 to 4 are shown together in Table 1.
[0113] [Table 1]
[0114] (Production of Coated Semiconductor Nanoparticles) Hereinafter, the method for producing coated semiconductor nanoparticles of the present invention was carried out using the semiconductor nanoparticles produced in Production Examples 1 to 4. Microwave irradiation was carried out using a microwave synthesis reaction apparatus (flexi WAVE, manufactured by Milestone General Co., Ltd.).
[0115] Example 1 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, and 50 μL of 25% ammonia (NH3) aqueous solution were mixed and added to a high-pressure reaction vessel. The mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450MHz, 60°C, for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and redispersed by adding toluene and performing ultrasonic irradiation treatment. The resulting coated semiconductor nanoparticles had a fluorescence emission efficiency of 72%. The rate of decrease in fluorescence emission efficiency compared to before the coating process was 5.3%.
[0116] Example 2 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g of cetyltrimethylammonium bromide were mixed and added to a high-pressure reaction vessel. The mixing ratio was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 60°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The resulting coated semiconductor nanoparticles had a fluorescence emission efficiency of 70%, and the rate of decrease in the fluorescence emission efficiency compared to before the coating process was 7.9%.
[0117] Example 3 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The mixing ratio was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate to H2O was 1:4.6. 。 Thereafter, the above microwave synthesis reaction apparatus was used to perform heating at 2450 MHz at 60°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and ultrasonic irradiation treatment was performed to redisperse the nanoparticles. The resulting coated semiconductor nanoparticles had a fluorescence emission efficiency of 70%, and the reduction rate of the fluorescence emission efficiency compared to before the coating process was 7.9%.
[0118] Example 4 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 0.092 g of aluminum isopropoxide, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The respective mixing ratios were semiconductor nanoparticles: aluminum isopropoxide (weight ratio) = 1: 0.92, NH3: aluminum isopropoxide (molar ratio) = 1: 0.89, and aluminum isopropoxide (molar ratio): H2O = 1: 4.6. Thereafter, using the above-mentioned microwave synthesis reaction device, heating was performed at 2450 MHz at 60 ° C for 10 minutes to perform metal oxide coating. The obtained coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and redispersed by adding toluene and performing ultrasonic irradiation treatment. The obtained coated semiconductor nanoparticles had a fluorescence emission efficiency of 68%, and the decrease rate of the fluorescence emission efficiency compared to before the coating process was 10.5%.
[0119] Example 5 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 0.153 g of titanium tetrabutoxide, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The respective mixing ratios were semiconductor nanoparticles:titanium tetrabutoxide (weight ratio) = 1:1.5, NH3:titanium tetrabutoxide (molar ratio) = 1:0.89, and titanium tetrabutoxide (molar ratio):H2O = 1:4.6. Thereafter, using the above-mentioned microwave synthesis reaction device, heating was performed at 2450 MHz at 60°C for 10 minutes to perform metal oxide coating. The obtained coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and redispersed by adding toluene and performing ultrasonic irradiation treatment. The obtained coated semiconductor nanoparticles had a fluorescence emission efficiency of 65%, and the decrease rate of the fluorescence emission efficiency compared to before the coating process was 14.5%.
[0120] Example 6 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 0.147 g of zirconium propoxide, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The mixing ratios of each were semiconductor nanoparticles:zirconium propoxide (weight ratio)=1:1.5, NH3:zirconium propoxide (molar ratio)=1:0.89, and zirconium propoxide (molar ratio):H2O=1:4.6. Thereafter, the above-mentioned microwave synthesis reaction device was used to heat the mixture at 60°C for 10 minutes at 2450 MHz to perform metal oxide coating. The obtained coated semiconductor nanoparticles were precipitated by centrifugation, the supernatant liquid was removed, and toluene was added and ultrasonic irradiation treatment was performed to redisperse the mixture. The resulting coated semiconductor nanoparticles had a fluorescence emission efficiency of 67%, and the rate of decrease in the fluorescence emission efficiency compared to before the coating process was 11.8%.
[0121] Example 7 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 50 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. At this time, the mixing ratio was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.47, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 60°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The fluorescent emission efficiency of the resulting coated semiconductor nanoparticles was 73%, and the rate of decrease in the fluorescent emission efficiency compared to before the coating process was 3.9%.
[0122] Example 8 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 200 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. At this time, the mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:1.9, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 60°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The resulting coated semiconductor nanoparticles had a fluorescence emission efficiency of 70%, and the rate of decrease in the fluorescence emission efficiency compared to before the coating process was 7.9%.
[0123] Example 9 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 300 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. At this time, the mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:2.8, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate to H2O was 1:4.6. 。 Thereafter, the above microwave synthesis reaction apparatus was used to perform heating at 2450 MHz at 60°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and ultrasonic irradiation treatment was performed to redisperse the nanoparticles. The fluorescent emission efficiency of the resulting coated semiconductor nanoparticles was 68%, and the rate of decrease in the fluorescent emission efficiency compared to before the coating process was 10.5%.
[0124] Example 10 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 25 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. At this time, the mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.45, tetraethyl OrthoThe molar ratio of silicate:H2O was 1:2.3. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 60°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The fluorescent emission efficiency of the resulting coated semiconductor nanoparticles was 73%, and the rate of decrease in the fluorescent emission efficiency compared to before the coating process was 3.9%.
[0125] Example 11 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 100 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. At this time, the mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:1.8, tetraethyl Ortho The molar ratio of silicate:H2O was 1:9.2. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 60°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The fluorescent emission efficiency of the resulting coated semiconductor nanoparticles was 68%, and the rate of decrease in the fluorescent emission efficiency compared to before the coating process was 10.5%.
[0126] Example 12 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 40°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The fluorescent emission efficiency of the resulting coated semiconductor nanoparticles was 73%, and the rate of decrease in the fluorescent emission efficiency compared to before the coating process was 3.9%.
[0127] (Example 13) 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. Then, using the microwave synthesis reaction device described above, the mixture was heated at 2450 MHz at 50° C. for 10 minutes to perform metal oxide coating. The obtained coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and redispersed by adding toluene and performing ultrasonic irradiation treatment. The fluorescent emission efficiency of the obtained coated semiconductor nanoparticles was 72%, and the decrease rate of the fluorescent emission efficiency compared to before the coating process was 5.3%.
[0128] Example 14 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl OrthoThe molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 80°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The resulting coated semiconductor nanoparticles had a fluorescence emission efficiency of 67%, and the rate of decrease in fluorescence emission efficiency compared to before the coating process was 11.8%.
[0129] Example 15 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 100°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The fluorescent emission efficiency of the resulting coated semiconductor nanoparticles was 62%, and the rate of decrease in the fluorescent emission efficiency compared to before the coating process was 18.4%.
[0130] Example 16 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 60°C for 3 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The fluorescent emission efficiency of the resulting coated semiconductor nanoparticles was 73%, and the rate of decrease in the fluorescent emission efficiency compared to before the coating process was 3.9%.
[0131] (Example 17) 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 60°C for 5 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The fluorescent emission efficiency of the resulting coated semiconductor nanoparticles was 73%, and the rate of decrease in the fluorescent emission efficiency compared to before the coating process was 3.9%.
[0132] (Example 18) 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 60°C for 15 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The fluorescent emission efficiency of the resulting coated semiconductor nanoparticles was 70%, and the rate of decrease in the fluorescent emission efficiency compared to before the coating process was 7.9%.
[0133] (Example 19) 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. Then, using the microwave synthesis reaction apparatus described above, the mixture was heated at 2450 MHz at 60°C for 20 minutes to perform metal oxide coating. The mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate to H2O was 1:4.6. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and the nanoparticles were redispersed by adding toluene and subjecting them to ultrasonic irradiation. The resulting coated semiconductor nanoparticles had a fluorescence emission efficiency of 69%, and the decrease in fluorescence emission efficiency compared to before the coating process was 9.2%.
[0134] (Example 20) 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. Then, using the microwave synthesis reaction apparatus described above, the mixture was heated at 2450 MHz at 60°C for 30 minutes to perform metal oxide coating. The mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate to H2O was 1:4.6. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and the nanoparticles were redispersed by adding toluene and subjecting them to ultrasonic irradiation. The resulting coated semiconductor nanoparticles had a fluorescence emission efficiency of 67%, and the rate of decrease in fluorescence emission efficiency compared to before the coating process was 11.8%.
[0135] Example 21 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 2, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl OrthoThe molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 60°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The fluorescent emission efficiency of the resulting coated semiconductor nanoparticles was 74%, and the rate of decrease in the fluorescent emission efficiency compared to before the coating process was 1.3%.
[0136] Example 22 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 3, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 60°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and redispersed by adding toluene and performing ultrasonic irradiation treatment. The resulting coated semiconductor nanoparticles had a fluorescence emission efficiency of 73%, and the rate of decrease in fluorescence emission efficiency compared to before the coating process was 1.4%.
[0137] Example 23 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 4, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia solution, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a high-pressure reaction vessel. The mixing ratio of each was semiconductor nanoparticles:tetraethyl orthosilicate (weight ratio) = 1:0.94, NH3:tetraethyl Ortho Silicate (molar ratio) = 1:0.89, tetraethyl Ortho The molar ratio of silicate:H2O was 1:4.6. The above microwave synthesis reaction apparatus was then used to heat the nanoparticles at 2450 MHz at 60°C for 10 minutes to perform metal oxide coating. The resulting coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and toluene was added and the nanoparticles were redispersed by ultrasonic irradiation. The fluorescent emission efficiency of the resulting coated semiconductor nanoparticles was 74%, and the rate of decrease in the fluorescent emission efficiency compared to before the coating process was 1.3%.
[0138] The manufacturing methods of Examples 1 to 23 are summarized in Table 2.
[0139] [Table 2]
[0140] Comparative Example 1 10 g of the 1.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1, 100 μL of tetraethyl orthosilicate, 50 μL of 25% aqueous ammonia, and 0.010 g / 100 μL of cetyltrimethylammonium bromide / ethanol solution were mixed and added to a flask. Then, the mixture was heated and stirred at 60° C. for 6 hours using a mantle heater to perform metal oxide coating. The obtained coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and redispersed by adding toluene and performing ultrasonic irradiation treatment. The fluorescent emission efficiency of the obtained coated semiconductor nanoparticles was 56%, and the decrease rate of the fluorescent emission efficiency compared to before the coating process was 35.7%, confirming a significant decrease in the fluorescent emission efficiency compared to the manufacturing method using microwave irradiation treatment.
[0141] Comparative Example 2 After adding 50 mL of cyclohexane, 1.2 g of polyoxyethylene (5) nonylphenyl ether (IGEPAL-CO520 manufactured by Rhodia), and 100 μL of tetraethyl orthosilicate, 5 g of the 2.0 wt% InP / ZnSe / ZnS semiconductor nanoparticle toluene solution obtained in Production Example 1 was added and stirred at room temperature of 25° C. While stirring, 1 mL of 10% ammonia aqueous solution was added little by little, and stirring was continued for 48 hours to perform metal oxide coating. The obtained coated semiconductor nanoparticles were precipitated by centrifugation to remove the supernatant, and redispersed by adding toluene and performing ultrasonic irradiation treatment. The obtained coated semiconductor nanoparticles had a fluorescence emission efficiency of 26%, and the decrease rate of the fluorescence emission efficiency compared to before the coating process was 65.8%, and a significant decrease in the fluorescence emission efficiency was confirmed compared to the manufacturing method using microwave irradiation treatment.
[0142] As described above, heating with a mantle heater instead of microwave irradiation treatment required a long time and the fluorescence emission efficiency was significantly reduced in Comparative Example 1. In Comparative Example 2, heating at room temperature for 48 hours was required, which was longer than Comparative Example 1, and the fluorescence emission efficiency was significantly reduced compared to Comparative Example 1.
[0143] On the other hand, in Examples 1 to 23, which are examples of the method for producing coated semiconductor nanoparticles of the present invention, it was confirmed that by using microwave irradiation treatment to coat the surfaces of semiconductor nanoparticles with metal oxide in a short period of time, the deterioration of fluorescence emission efficiency in the coating process is suppressed, and coated semiconductor nanoparticles exhibiting high fluorescence emission efficiency can be efficiently produced.
[0144] (Method of manufacturing wavelength converting material) The coated semiconductor nanoparticles obtained in Examples 1 to 23 and Comparative Examples 1 and 2, and the semiconductor nanoparticles obtained in Production Example 1 were used as they were without coating as Comparative Example 3 to prepare wavelength converting materials. 1.0 g of a 1.0 wt% toluene solution of the above semiconductor nanoparticles or coated semiconductor nanoparticles was mixed with 10.0 g of silicone resin (LPS-5547 manufactured by Shin-Etsu Chemical Co., Ltd.) and heated at 60°C while stirring to remove the solvent under reduced pressure. After that, the mixture was vacuum degassed and applied onto a polyethylene terephthalate (PET) film with a thickness of 50 μm, and a semiconductor nanoparticle resin layer with a thickness of 100 μm was formed by a bar coater. Furthermore, a PET film was attached onto this resin layer and laminated. This film was heated at 60°C for 2 hours and then at 150°C for 4 hours to harden the semiconductor nanoparticle resin layer, thereby preparing a wavelength converting material.
[0145] The obtained wavelength converting material was treated for 100 hours under conditions of 85°C and 85% RH (relative humidity), and the fluorescence emission efficiency of the wavelength converting material after the treatment was measured to evaluate its reliability. Table 3 shows the fluorescence emission efficiency after preparation of the wavelength converting material and the fluorescence emission efficiency after reliability evaluation.
[0146] [Table 3]
[0147] As shown in Table 3, the fluorescence efficiency of the wavelength converting material after the reliability evaluation was 17% in Comparative Example 1, 9% in Comparative Example 2, and 17% in Comparative Example 3, and thus the fluorescence efficiency after the reliability evaluation was below 20% in all Comparative Examples.
[0148] On the other hand, the coated semiconductor nanoparticles (Examples 1 to 23) produced by the method for producing coated semiconductor nanoparticles of the present invention had a fluorescence emission efficiency of 20% or more after reliability evaluation. As described above, the coated semiconductor nanoparticles produced by the method for producing coated semiconductor nanoparticles of the present invention exhibit high stability, and it was confirmed that the wavelength conversion material using these exhibits suppressed deterioration of fluorescence emission efficiency under high temperature and high humidity conditions and is highly reliable. Thus, the coated semiconductor nanoparticles produced by the method for producing coated semiconductor nanoparticles of the present invention have better physical properties as a material than conventional materials and are clearly different from conventional materials.
[0149] The present invention is not limited to the above-described embodiment. The above-described embodiment is merely an example, and anything that has substantially the same configuration as the technical idea described in the claims of the present invention and exhibits similar effects is included in the technical scope of the present invention.
Claims
1. A method for producing coated semiconductor nanoparticles, comprising a step of coating a surface of semiconductor nanoparticles with a metal oxide, The semiconductor nanoparticles used in the coating step include a semiconductor nanoparticle core and one or more semiconductor nanoparticle shells covering the semiconductor nanoparticle core; The coating step is carried out in a solvent containing 90% or more of a non-polar solvent by volume ratio, The processing time of the microwave irradiation treatment in the coating step is in the range of 3 to 30 minutes, The heating temperature of the microwave irradiation treatment in the coating step is in the range of 40 to 100° C., The semiconductor nanoparticle core is InP, the semiconductor nanoparticle shell is ZnS, ZnSe, and the semiconductor nanoparticle is InP / ZnSe / ZnS; a metal oxide precursor is subjected to a microwave irradiation treatment to coat the surface of the semiconductor nanoparticles with the metal oxide; A method for producing coated semiconductor nanoparticles, characterized in that the metal in the metal oxide is any one of zinc (Zn), iron (Fe), yttrium (Y), aluminum (Al), zirconium (Zr), titanium (Ti), and hafnium (Hf).
2. 2. The method for producing coated semiconductor nanoparticles according to claim 1, characterized in that the coating step is carried out in the coexistence of the semiconductor nanoparticles and the metal oxide precursor, and the metal oxide precursor in the coexistence is subjected to the microwave irradiation treatment, thereby coating the surface of the semiconductor nanoparticles with the metal oxide.
3. 3. The method for producing coated semiconductor nanoparticles according to claim 1, wherein the non-polar solvent used in the coating step is one or more of toluene, hexane, cyclohexane, benzene, and diethyl ether.
4. The method for producing coated semiconductor nanoparticles according to any one of claims 1 to 3, characterized in that the metal oxide precursor used in the coating step is selected from the group consisting of metal alkoxides, metal halides, and metal complexes, either singly or in combination.
5. The method for producing coated semiconductor nanoparticles according to any one of claims 1 to 4, characterized in that the coating step is carried out in the presence of an alkaline aqueous solution.
6. The method for producing coated semiconductor nanoparticles according to any one of claims 1 to 5, characterized in that the coating step is carried out in the presence of a surfactant.
7. The method for producing coated semiconductor nanoparticles according to any one of claims 1 to 6, characterized in that the coating step is carried out in the presence of an alcohol.
8. The method for producing coated semiconductor nanoparticles according to any one of claims 1 to 7, further comprising a step of modifying the surfaces of the semiconductor nanoparticles with a surface modifier prior to the coating step.
9. 9. The method for producing coated semiconductor nanoparticles according to claim 8, wherein the surface modifier is selected from the group consisting of (3-aminopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane, (3-mercaptopropyl)trimethoxysilane, (3-mercaptopropyl)triethoxysilane, 6-mercapto-1-hexanol, mercaptoacetic acid, 3-mercaptopropionic acid, and 4-mercaptobenzoic acid, either alone or in combination.
Citation Information
Patent Citations
Process for preparing water soluble CdTe / CdS nuclear / shell type quantum point by microwave radiation reaction
CN1693207A
Liquid crystal display
JP2012022028A
Method for producing covered semiconductor nanoparticle
JP2017025219A
Low cadmium nanocrystal quantum dot heterostructure
JP2018534784A
Cadmium-free quantum dot, production method of the same, composition and composite comprising the same, and display element
JP2019123866A